Faecal immunochemical testing and blood tests for prioritization of urgent colorectal cancer referrals in symptomatic patients: a 2-year evaluation. Issue 2 (9th March 2021) - Bailey, J A; Weller, J; Chapman, C J; Ford, A; Hardy, K; Oliver, S; Morling, J R; Simpson, J A; Humes, D J; Banerjea, A
Abstract: Background: A novel pathway incorporating faecal immunochemical testing (FIT) for rapid colorectal cancer diagnosis (RCCD) was introduced in 2017. This paper reports on the service evaluation after 2 years of pathway implementation. Methods: The RCCD protocol was based on FIT, blood results and symptoms to stratify adult patients in primary care. Two-week-wait (2WW) investigation was indicated for patients with rectal bleeding, rectal mass and faecal haemoglobin (fHb) level of 10 µg Hb/g faeces or above or 4 µg Hb/g faeces or more in the presence of anaemia, low ferritin or thrombocytosis, in all other symptom groups. Patients with 100 µg Hb/g faeces or above had expedited investigation . A retrospective audit of colorectal cancer detected between 2017 and 2019 was conducted, fHb thresholds were reviewed and critically assessed for cancer diagnoses. Results: In 2 years, 14788 FIT tests were dispatched with 13361 (90.4 per cent) completed returns. Overall, fHb was less than 4 µg Hb/g faeces in 9208 results (68.9 per cent), 4–9.9 µg Hb/g in 1583 (11.8 per cent), 10–99.9 µg Hb/g in 1850 (13.8 per cent) and 100 µg Hb/g faeces or above in 720 (5.4 per cent). During follow-up (median 10.4 months), 227 colorectal cancers were diagnosed. The cancer detection rate was 0.1 per cent in patients with fHb below 4 µg Hb/g faeces, 0.6 per cent in those with fHb 4–9.9 µg Hb/g faeces, 3.3 per cent for fHb 10–99.9 µg Hb/g faeces and 20.7 per cent for fHb 100 µg Hb/g faeces or above. The detection rate in the cohort with 10–19.9 µg Hb/g faeces was 1.4 per cent, below the National Institute for Health and Care Excellence threshold for urgent referral. The colorectal cancer rate in patients with fHb below 20 µg Hb/g faeces was less than 0.3 per cent. Conclusion: Use of FIT to "rule out" urgent referral from primary care misses a small number of cases. The threshold for referral may be adjusted with blood results to improve stratification . Abstract : We present outcome data from a service evaluation that demonstrates clinical effectiveness and safety. This strategy may be crucial to overcoming the effects of the Coronavirus pandemic on 2WW and urgent pathways.